Infrared and 13C, 15N and 119Sn NMR spectral study of some tri- and diorganotin(IV) pyridinecarboxylates - Lébl, Tomáš; Holeček, Jaroslav; Lyčka, Antonín (Univerzita Pardubice, 1996)
Eleven organotin(IV) pyridinecarboxylates of general formula R3SnOOCR´ and R2Sn(OOCR´)2 where R is 1-butyl or phenyl and R´ is 2-, 3- or 4- pyridyl were prepared. Structures of these compounds in the solid state and in solutions of non-coordinating solvent (CDCl3) and coordinating solvent ((CD3)2SO) were studied using IR spectroscopy, multinuclear (13C, 15N, 119Sn) NMR spectroscopy and 119Sn CP MAS spectroscopy.